PROGRAM PENANAMAN POHON OLEH PRAMUKA DALAM UPAYA MENGHIJAUKAN LINGKUNGAN PERMUKIMAN MASYARAKAT TANJUNG SARI - Heka Maya Sari Br Sembiring; Elsa Septiani; Esamica Sihombing; Asnita Roulina Sirait; Enjelina Br Ginting; Putri Heriwanti Manik (ASOSIASI IDEBAHASA KEPRI, 2026)
The tree-planting program conducted by the Scouts in Gg. Rahmat Tanjung Sari is a form of community service aimed at supporting environmental greening efforts in residential areas. This study uses a qualitative descriptive approach, with data collection techniques involving observation and documentation. The research focus includes the planning, implementation, and results of the tree-planting activities. The activities were carried out on December 15–16, 2025, by planting five trees on a resident's land that was previously unmanaged. The results of the study indicate that the tree-planting program can provide a positive impact on environmental conditions, particularly in improving the quality of the residential environment and the aesthetic value of the area. Although the implementation of the activity was carried out entirely by the Scout team without direct community involvement, it still provided ecological benefits and has the potential to increase public awareness regarding the importance of environmental conservation. This program also demonstrates the strategic role of the Scouts as a youth organization in community service activities oriented toward environmental preservation.